Mapping the Hispanic migration trends - Moreno Fernández, Francisco; Álvarez Mella, Héctor; Scheffler, David (HCIAS working papers on Ibero-America, 2024)
This compact atlas presents several maps that attempt to outline the main keys to Spanish as a migratory language. From a historical perspective, it maps the first Spanish migration flows in the Americas and the main regional origins of the first settlers, the evolution of the ethnic composition of the population and migratory movements of communities such as the Italian, which influenced American Spanish. From a current perspective, the maps presented show the current trends of Latin American migration in the continent, from Central American flows to Hispanic migration to the United States and more recently to European destinations.
Gesehen am 30.04.2024